A Novel Method of Sterilizing Orthodontic Instruments - Miller Jo-Ann; Harrower Keith M.; Costello Maurice J. (Australasian Orthodontic Journal, 1992)
A range of orthodontic instruments was artificially inoculated with a mixed culture of representatives of the oral microflora and a marker bacterium and subjected to dry heat sterilization using a glass bead sterilizer. The shortest time which would guarantee total sterilization of the functional parts of the instruments was thirty seconds.